Upaya peningkatan pengetahuan dan keterampilan masyarakat tentang pertolongan pertama pada luka dengan perdarahan - Erwin Erwin; Hellena Deli; Wan Nishfa Dewi; Yulia Rizka (Unri Conference Series: Community Engagement, 2022)
This activity aims to increase the knowledge and skills of the community regarding the handling of wounds accompanied by bleeding. The methods used are lectures, questions and answers, and demonstrations related to first aid for wounds accompanied by bleeding. The activity is carried out with health cadres and the community in the Maharatu district, Subdistrict Marpoyan Damai. The number of participants who attended was 30 people. Before the material presentation, the respondent filled out a questionnaire, then continued with the provision of materials related to wounds, and the management of bleeding and then accompanied by demonstrations of how to first aid for wounds accompanied by bleeding. After the material presentation, the community was asked to fill out a questionnaire and re-demonstrate how to first aid wounds accompanied by bleeding. The results of this activity indicate that there was an increase in public knowledge regarding first aid for wounds accompanied by bleeding after counseling. Besides that the public could demonstrate first aid for wounds accompanied by bleeding. After this activity, the community has been able to perform first aid on wounds with bleeding independently at home.